Determining the frequency of morphological characteristics in a sample of Brazilian children - Eduardo Perrone; Thais Arbocese Zanolla; Rodrigo Ambrosio Fock; Ana Beatriz Alvarez Perez; Decio Brunoni (Brazilian Society of Pediatrics, 2017)
Objective: To establish the frequency of 82 morphological features in a sample of Brazilian children (between 3 and 13 years old), to understand the influence of age, gender, and ethnicity. Methods: This was a cross‐sectional study that evaluated 239 children with typical development (between 3 and 13 years old) regarding the presence of 82 morphological characteristics. A previously described protocol, based on the London Dysmorphology Database, was applied to evaluate the sample. This protocol was culturally adapted to Brazilian Portuguese. Results: The frequency of 82 morphological characteristics was established in the sample; of 82 characteristics, 50% were considered morphological anomalies (frequency less than 4%). At least 25% of the sample presented more than one minor morphological anomaly. Age was shown to influence the frequency of the following morphological characteristics: widow's peak, prominent antihelix, prominent upper lip, irregular or crowded teeth, and clinodactyly, but had no influence on the frequency of minor morphological anomalies. Gender influenced dysplastic ears and attached earlobe, but had no influence on the frequency of minor morphological anomalies; ethnicity showed influence on camptodactyly and prominent antihelix. A statistically significant divergence was observed regarding 43 of the 73 morphological characteristics that could be compared with literature data (58.9%). Conclusions: The study determined the frequency of 82 morphological characteristics in 239 children with typical development. Age was the variable that showed more influence on the frequency of morphological characteristics, and comparison with literature data showed that the frequency depends on variables such as age and ethnicity.